2018
DOI: 10.1016/j.brainres.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Secondary traumatic stress increases expression of proteins implicated in peripheral and central sensitization of trigeminal neurons

Abstract: The pathology of migraine, a common neurological disease, involves sensitization and activation of trigeminal nociceptive neurons to promote hyperalgesia and allodynia during an attack. Migraineurs often exhibit characteristics of a hyperexcitable or hypervigilant nervous system. One of the primary reported risk factors for development of a hyperexcitable trigeminal system is chronic, unmanaged stress and anxiety. While primary traumatic stress is a commonly cited risk factor for many pain conditions, exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 53 publications
1
15
0
Order By: Relevance
“…Similar to our data, Hawkins showed that secondary traumatic stress increases GFAP and leads to trigeminal sensitization, and dental injuries can lead to GFAP activation through ocular inflammation . As GFAP is directly associated with neural damage, inflammation in any structure related to the trigeminal ganglion seems to lead to neuroinflammation and altered behavior due to discomfort in the head and neck region and the blockage of TNF‐α pathway was important to attenuates GFAP overexpression, neuroinflammation, and oral discomfort in this ODI experimental model.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to our data, Hawkins showed that secondary traumatic stress increases GFAP and leads to trigeminal sensitization, and dental injuries can lead to GFAP activation through ocular inflammation . As GFAP is directly associated with neural damage, inflammation in any structure related to the trigeminal ganglion seems to lead to neuroinflammation and altered behavior due to discomfort in the head and neck region and the blockage of TNF‐α pathway was important to attenuates GFAP overexpression, neuroinflammation, and oral discomfort in this ODI experimental model.…”
Section: Discussionsupporting
confidence: 88%
“…26,27 ERK activation in TG neurons is also induced by migraine or lingual nerve crush. 26,37,38 Our results showed that intra-TG injection of CXCL10 induced CXCR3dependent activation of ERK, but not p38 or JNK, in WT mice, suggesting that ERK is a downstream kinase of CXCL10/CXCR3. Inhibition of ERK activation by PD98059 (MEK inhibitor) has been shown to attenuate pIONL-induced mechanical allodynia and lingual nerve crush-induced pain hypersensitivity.…”
Section: Cxcl10/cxcr3 Induces Trigeminal Neuropathic Pain Via Activatmentioning
confidence: 60%
“…It has been shown that ligation of the ION induces the activation of ERK and p38, but not JNK in the TG [ 24 , 25 ]. ERK is also activated in TG neurons induced by migraine or lingual nerve crush [ 24 , 44 , 45 ]. We showed that the pIONL-induced ERK activation was reduced in Tlr8 −/− mice.…”
Section: Discussionmentioning
confidence: 99%